2021
DOI: 10.3389/fvets.2021.725737
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of a Nalidixic Acid-Resistant Salmonella Enteritidis Strain Causing Persistent Infections in Broiler Chickens

Abstract: Virulent strains of Salmonella enterica subsp. enterica serovar Enteritidis (SE) harbored by poultry can cause disease in poultry flocks and potentially result in human foodborne illness. Two broiler flocks grown a year apart on the same premises experienced mortality throughout the growing period due to septicemic disease caused by SE. Gross lesions predominantly consisted of polyserositis followed by yolk sacculitis, arthritis, osteomyelitis, and spondylitis. Tissues with lesions were cultured yielding 59 SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…According to newly available data, more than 60 billion chickens are consumed annually ( 23 ), highlighting the importance of chicken consumption in the diet of populations across the world. At the same time, poultry farms are considered a favorable biotope for the development of many pathogens like Salmonella , causing huge economic losses for producers ( 6 , 8 , 18 , 24 ). Hence, to provide in-depth data about the AMR and virulence of Salmonella isolates causing poultry death, we used WGS combined with accurate phenotypic assays to analyze a collection of 105 Salmonella isolates recovered from dead poultry between 2008 and 2019, in 95 farms representing all 17 cities of Shandong province.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to newly available data, more than 60 billion chickens are consumed annually ( 23 ), highlighting the importance of chicken consumption in the diet of populations across the world. At the same time, poultry farms are considered a favorable biotope for the development of many pathogens like Salmonella , causing huge economic losses for producers ( 6 , 8 , 18 , 24 ). Hence, to provide in-depth data about the AMR and virulence of Salmonella isolates causing poultry death, we used WGS combined with accurate phenotypic assays to analyze a collection of 105 Salmonella isolates recovered from dead poultry between 2008 and 2019, in 95 farms representing all 17 cities of Shandong province.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Wang et al reported the dominance of S. Enteritidis in isolates recovered from dead-in-shell chicken embryos in Northern China ( 25 ). Furthermore, a study performed by the Walker group demonstrated the implication of S. Enteritidis in persistent infections in broiler chickens in North Carolina ( 24 ). Generally, avian salmonellosis has been linked for decades to isolates of S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A clonal group of S. enteritidis known as SE86, a frequently identified poultry Salmonella isolate in Brazil associated with foodborne outbreaks, has been reported to be resistant to ciprofloxacin (41.9%) and sulfafurazole (75%) [ 121 ]. A persistent septicemia causing S. enteritidis (SE_TAU19) resistant to nalidixic acid and sulfadimethaxine was reported [ 162 ]. Quesada et al [ 130 ] found the mcr-1 gene (colistin resistance) in E. coli and S. enterica from poultry and swine.…”
Section: Poultry Production Systems and Amr Bacteriamentioning
confidence: 99%